Capital Structure, Accounting Conservatisne, Intellectual Capital and Financial Performance: Its Impact on Stock Prices - Dendi Purnama (Universitas Kuningan, 2019)
This study aims to analyze the effect of capital structure proxied by DAR and DER, accounting conservatism and intellectual capital on financial performance that is proxied by ROA and ROE and analyze the effect of financial performance proxied by ROA and ROE on stock prices. The population in this study were all property and real estate sub-sector service companies listed on the Indonesia Stock Exchange from 2014 to 2018. The sample in this study were 39 companies for 5 years. The method used in this research is descriptive and verification methods. The analysis used in this study is panel data regression. The findings show the debt to asset ratio, and debt to equity ratio have a negative effect on return on assets and return on equity. Accounting conservatism has a positive effect on return on assets while conservatism and intellectual capital have no effect on return on equity. Intellectual Capital has a positive effect on return on assets. Return on assets has a significant positive effect on stock prices while return on equity has no effect on stock prices Key words : Capital Structure, Accounting Conservatisne, Intellectual Capital and Financial Performance, Stock Prices